2010
DOI: 10.1111/igc.0b013e3181a9026d
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics-Based Approach Identified Differentially Expressed Proteins With Potential Roles in Endometrial Carcinoma

Abstract: Our results suggested that these identified proteins, including epidermal fatty acid-binding protein, calcyphosine, and cyclophilin A, might be of potential values in the studies of endometrial carcinogenesis or investigations of diagnostic biomarkers or treatment targets for endometrial carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…Survival analysis has indicated that CAPS is a potential survival predictor in breast cancer patients receiving adjuvant tamoxifen (25). Previous studies also revealed that CAPS was an independent prognostic factor for endometrial cancer patients (15,24) and colorectal cancer patients (17 (Fig. 3).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Survival analysis has indicated that CAPS is a potential survival predictor in breast cancer patients receiving adjuvant tamoxifen (25). Previous studies also revealed that CAPS was an independent prognostic factor for endometrial cancer patients (15,24) and colorectal cancer patients (17 (Fig. 3).…”
Section: Discussionmentioning
confidence: 89%
“…For example, CAPS was significantly down regulated in the bronchoalveolar lavage fluid of sulfur mustard-exposed patients when compared with healthy controls (12). Previous studies also showed that CAPS was overexpressed in ovarian cancer (13), ependymoma (14), endometrial cancer (15), lung cancer (16) and colorectal cancer (17). Another previous study revealed that CAPS promoted cancer progression and may be a prognostic indicator in colorectal cancer patients (17).…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, increase in both E-FABP and CAPS in relation to EC were also reported in a different paper [12]. Implementing this method, both papers conclude that the overexpression of E-FABP and CAPS is correlated to histodifferentiation but not to clinical staging [11,12].…”
Section: Proteomicsmentioning
confidence: 83%
“…A study performed by Li et al exemplifies the value of proteomics where three potential EC-associated proteins were identified; Cyclophilin A (CypA), epidermal fatty acid-binding protein (E-FABP), and caclyphosine (CAPS) [11]. Additionally, increase in both E-FABP and CAPS in relation to EC were also reported in a different paper [12]. Implementing this method, both papers conclude that the overexpression of E-FABP and CAPS is correlated to histodifferentiation but not to clinical staging [11,12].…”
Section: Proteomicsmentioning
confidence: 94%
“…It is phosphorylated in a cAMP-dependent manner and thus may be implicated in the cross-signaling between these cascades to coordinate cell proliferation and differentiation (9), suggesting its involvment in carcinogenesis. It has been proven that CAPS is expressed in many tumors; overexpression of CAPS occurs in ependymoma (23), lung cancer (24), ovarian cancer (25) and endometrial cancer (26).…”
Section: Discussionmentioning
confidence: 99%